Routes and difficulties of research with children in contexts of arrivals and departures: reflections on research in programs institutional care - Roseli Nazário; Kamila Barros Tizatto (Universidade Federal de Santa Catarina, 2019)
This article shared an articulated analysis based on two researches with children in institutional care programs implemented in Santa Catarina. The objective was to shed light on the theoretical-methodological processes adopted by which research, in order to place in a point of view, intersect: i) the posts put in for entry into the field, under a strong tension between the right of protection and the right of children to participate; ii) emergence through communicative actions involving children in research, built on how they are capable and the children. Its theoretical basis is based on the Studies of Childhood, at the same time as it refers to the generation and how children as plural social actors in their modes of action.